Anti-NMDA receptor antibodies in patients with a first episode of schizophrenia - Masopust J (Dove Medical Press, 2015)
Jirí Masopust,1,2 Ctirad Andrýs,3 Jan Bažant,1 Oldrich Vyšata,4 Kamil Kuca,5 Martin Vališ4 1Department of Psychiatry, Faculty of Medicine in Hradec Kralové, Charles University in Prague, University Hospital Hradec Králové, Hradec Králové, Czech Republic; 2National Institute of Mental Health, Klecany, Czech Republic; 3Institute of Clinical Immunology and Allergology, Charles University in Prague, Faculty of Medicine in Hradec Králové, and University Hospital Hradec Králové, Hradec Králové, Czech Republic; 4Department of Neurology, Charles University in Prague, Faculty of Medicine in Hradec Králové, and University Hospital Hradec Králové, Hradec Králové, Czech Republic; 5Biomedical Research Centrum, University Hospital Hradec Králové, Hradec Králové, Czech Republic Background: Encephalitis with antibodies against N-methyl-D-aspartate receptor (NMDA-R) is classified as an autoimmune disorder with psychotic symptoms, which are frequently dominant. However, it remains unclear how frequently NMDA-R antibodies lead to a condition that mimics psychosis and first-episode schizophrenia. In our work, we investigated the presence of antibodies against NMDA-R in patients with first-episode psychosis (FEP) in comparison with healthy volunteers.Methods: This study included 50 antipsychotic-naïve patients with FEP (including 21 women) and 50 healthy volunteers (including 21 women). The mean age of the patients was 27.4 (±7.4) years and that of the healthy controls was 27.0 (±7.3) years. Antibodies against NMDA-R in the serum were detected by immunofluorescence.Results: None of the investigated patients with an FEP and none of the healthy controls showed positive antibodies against NMDA-Rs.Conclusion: According to results of studies, a small proportion of patients with an FEP possess antibodies against NMDA-R. However, the extent to which this finding contributes to the etiopathogenesis of the response to antipsychotic medication and whether immunomodulatory therapy is indicated in these cases remains uncertain. Keywords: N-methyl-D-aspartate receptor, NMDA-R, encephalitis, schizophrenia